Avaliação dos níveis plasmáticos de VEGF em idosos com transtorno depressivo maior - Lucelia Scarabeli Silva Barroso (2016)
Major depressive disorder (MDD) is the leading psychiatric and multifactorial disorder. In relation to the elderly population, the prevalence of MDD is 7%, accounting for 1.6% of disability in this age group. Vascular endothelial growth factor (VEGF) is one of the factors that have been correlated with the etiology and / or development of this disease, but the information about its role in MDD is still limited, mainly in relation to the elderly population. The objective of this study was to evaluate the VEGF plasma concentration in elderly patients diagnosed with MDD, associating them with clinical parameters. The subjects were recruitedat the Psychogeriatric Outpatient Clinic of the Jenny de Andrade Faria Institute, Hospital das Clínicas, UFMG. We included elderly individuals with MDD (n = 39) and without other psychiatric diagnoses, and without history or evidence of dementias. Subjects without depression were used as controls (n = 31). All subjects were clinically evaluated by psychiatrists and neuropsychologists with the help of the MINI-Plus tool. HDRS-21 was used to assess the severity of depressive symptoms. Demographic data, the presence of clinical comorbidities and the medications used by the participants were also collected. Plasma was obtained from whole blood collected in EDTA tube and stored at -80 ° C until analysis. Plasma VEGF was measured by immunoassay (Luminex® technology - Merck-Millipore®). The results showed that plasma levels of VEGF aredecreased in the elderly with TDM (Depression Group) in relation to the elderly controls (Control Group). Our results showed that when stratified into mild depression, late onset and single episode, these elderly individuals have been shown decreased levels of VEGF. Correlation analyzes were performed and we found a negative correlation between VEGF levels in early-onset depression with mild depressive symptoms. We concluded, therefore, that VEGF is a potential marker for the onset of TDM, especially in the elderly. Our results also reinforce the relevance of vascular changes in geriatric depression with the reduction of VEGF levels in the elderly with late-onset MDD, and this growth factor may bethe link between these two situations.